1993
DOI: 10.1136/jcp.46.8.730
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypercholesterolaemia: pilot study to identify children at risk.

Abstract: 70-5% of samples tested. Forty two (21%) of patients tested had a borderline cholesterol (5.2-5.9 mmol/l) but 50% of these fell within the normal range when fasting capillary samples were analysed. Children with significant hypercholesterolaemia on random testing (concentrations of >5.9 mmol/) (8.5%) also had fasting venous blood assayed for high density lipoprotein (HDL) cholesterol and tri-glyceride in the laboratory. Results indicated that 6*5% of patients screened were at high risk of cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A pilot study in the UK evaluated a method of identifying FH children in one geographic location. 68 The authors calculated that only ten of the estimated 300 children with FH in the area had been identified. High-risk patients were defined as men aged under 50 years and women aged below 55 years who had an MI or angina.…”
Section: In Children Of High-risk Individualsmentioning
confidence: 99%
“…A pilot study in the UK evaluated a method of identifying FH children in one geographic location. 68 The authors calculated that only ten of the estimated 300 children with FH in the area had been identified. High-risk patients were defined as men aged under 50 years and women aged below 55 years who had an MI or angina.…”
Section: In Children Of High-risk Individualsmentioning
confidence: 99%
“…The observation that wives of MI patients may be at a higher risk of developing CAD in the future cannot be explained through genetic similarities with their husbands, as in the cases of the relatives of MI patients [16][17][18]. Therefore, attention should be focused to the lifestyle, especially smoking (active and/or passive), dietary habits (total fat intake, saturated, monounsaturated, polyunsaturated fatty acid intake, antioxidants and alcohol intake, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that if a MI patient has low HDL-C and high TG levels, then a lipid profile should be recommended to their first-degree relatives [16]. In another study, parameters were analysed in 200 children who were first-or second-degree relatives of patients with CAD [17]. The researchers reached the conclusion that children with familial hypercholesterolaemia can be indicated through the measurement of TC in the capillaries.…”
Section: Discussionmentioning
confidence: 99%